Resistance toward Domination of Racial Difference Ideology in Jacqueline Woodson’s Novels - Muhammad Al Hafizh (Bina Nusantara University, 2018)
This article was a result of the library research which was conducted by using Gramscian hegemony theory and ideology concept by Thompson. The media analized was the three novels by Jacqueline Woodson, they were Maizon at Blue Hill (MBH), If You Come Softly (IYCS), and Lena. The analysis of ideology use language, continued by the process of resitance, and finaly ideology negotiation. The result of the research shows that there are five resistance forms toward domination and ideology dissemination of racial differences in Jacqueline Woodson’s novels, they are (1) moderation, (2) pretention, (3) devaluation, (4) respectful resignation, and (5) rejection.